Pengaruh Ekstrak Etanolik Buah Takokak (Solanum torvum Swartz) terhadap Aktivitas Fagositosis pada Mencit Putih Jantan Balb/C dengan Metode Bersihan Karbon - R. F. X. Premihadi Putra; Jason Merari Peranginangin; Reslely Harjanti (Jurnal Farmasi Indonesia, 2014)
Solanum torvum Swartz (Solanaceae), known as takokak is a medicinal plant which has phagocytosis activity. Takokak plant usage with intent to suppress or reduce viral and bacterial intracellular infections, to improve immunodeficiency condition or as growth stimulant of body's immune cells in the immune system. This study was aimed to determine ability of takokak extract to increase the phagocytosis activity. This study used eight groups of white male mice each group six mice. Mice were given the test preparation once daily for seven days sequently. Group I: negative control 1% CMC-Na; group II: positive control dexamethasone 2 mg/kg bw mice; group III until VIII were given takokak ethanol extract dose of 37.5 mg/kg bw, 75 mg/kg bw, 150 mg/kg bw, 400 mg/kg bw, 500 mg/kg bw, 600 mg/kg bw respectively. Phagocytosis activity test data were analyzed using one way ANOVA test. The results showed that ethanol extract of takokak could increasing the phagocytosis activity and capacity of macrophages in Balb/c mice induced carbon clearance with carbon dose of 5 mg/kg bw.